2017
DOI: 10.5116/ijme.5a2e.a8b4
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of emotional intelligence in emergency medicine resident physicians

Abstract: ObjectivesTo define the emotional intelligence (EI) profile of emergency medicine (EM) residents, and identify resident EI strengths and weaknesses. MethodsFirst-, second-, and third-year residents (post-graduate years [PGY] 1, 2, and 3, respectively) of Thomas Jefferson University Hospital’s EM Program completed the Emotional Quotient Inventory (EQ-i 2.0), a validated instrument offered by Multi-Health Systems. Reported scores included total mean EI, 5 composite scores, and 15 subscales of EI. Scores are repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
2
0
2
Order By: Relevance
“…This is an interesting finding as previous studies had found that burnout tends to be especially prevalent in the early years of training, particularly in the transition from end of PGY-1 year into PGY-2 [ 6 ] . Another study had found that PGY-2 residents had lowest scores on an Emotional Quotient Inventory (EQ-i) compared to their peers [ 7 ]. If their resilience score being low was consistent with a level of burnout this would be consistent with those studies.…”
Section: Discussionmentioning
confidence: 99%
“…This is an interesting finding as previous studies had found that burnout tends to be especially prevalent in the early years of training, particularly in the transition from end of PGY-1 year into PGY-2 [ 6 ] . Another study had found that PGY-2 residents had lowest scores on an Emotional Quotient Inventory (EQ-i) compared to their peers [ 7 ]. If their resilience score being low was consistent with a level of burnout this would be consistent with those studies.…”
Section: Discussionmentioning
confidence: 99%
“…1 An assessment of EI in emergency medicine residents suggested that EI was higher in females (107) than the males (101). 2 Comparative study on EI and quality of care practices by nurses and doctors towards their patients concluded that patients perceived their medical officers (MOs) as having more EI than the nurses. 3 EI is a solid forecaster of a medical residents' wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…La Inteligencia Emocional (IE) es definida como la habilidad de percibir e identificar tanto las emociones propias como las ajenas, utilizando dicha información para guiar el pensamiento y actuar en consecuencia. Existen, por lo tanto, cuatro competencias principalmente relacionadas: 1) la capacidad para percibir emociones; 2) usar las emociones para facilitar el pensamiento; 3) comprender las emociones, y 4) manejar las mismas (2).…”
Section: Introductionunclassified